Neuropsychological response to ventriculoperitoneal shunting in idiopatic normal pressure hydrocephalus: early gains and the importance of baseline cognition - Yetim, Ezgi; Charehsaz, Amin; Çekiç, Efecan; Akyay, Ayşe; Işıkay, Ahmet İlkay and Yalçın Çakmaklı, Gül and Göçmen, Rahşan and Elibol, Bülent (Acta Medica, 2025)
Objective: Idiopathic normal pressure hydrocephalus (iNPH) is a reversible cause of cognitive impairment in older adults, characterized by gait disturbance, urinary incontinence, and cognitive decline. While ventriculoperitoneal (VP) shunt surgery can improve the classical triad, its cognitive and emotional effects remain under characterized. In this study we aim to investigate neuropsychiatric outcomes following VP shunt surgery in iNPH patients and to identify predictors of postoperative cognitive improvement. Material and Methods: This retrospective single-center study included 55 patients with iNPH who underwent VP shunt surgery between 2020 and 2024. Neuropsychological testing was conducted preoperatively and at a median of 11 months postoperatively, evaluating global cognition, memory, attention, executive and visuospatial functions, and mood. Pre- and postoperative performances were compared, and multivariate regression models were used to determine independent predictors of cognitive gain. Results: Significant postoperative improvements were observed in MMSE (median 24.0 to 27.0, p < 0.001), memory scores (ERCT: 40.0 to 45.0, p < 0.001), attention/executive functions and depression severity (BDI: 12.0 to 9.0, p < 0.001). Stratified regression analysis showed that patients in the lowest baseline MMSE and ERCT tertile experienced the greatest improvement shortly after surgery, with longer follow-up associated with diminishing gains (MMSE: β = –0.76, p < 0.001, ERCT: β = –0.76, p < 0.001). Conclusion: Cognitive improvement after VP shunt surgery in iNPH is strongly influenced by baseline cognitive status and the timing of follow-up. Patients with lower preoperative scores benefit the most when evaluated in the early postoperative phase. These findings emphasize the need for timely intervention and tailored neuropsychological monitoring to optimize outcomes.